10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Implantable phakic contact lens (IPCL) V2.0 has a special patterned hole on the leading left corner to ensure correct orientation and positioning. Incorrect orientation is an absolute indication for repositioning. We emphasize that incorrect orientation of a toric IPCL can induce significant refractive error and should be promptly recognized and corrected through timely lens repositioning.